Attributes of True and Deceptive Statements Made in Evaluations of Criminal Defendants. Issue 5 (19th October 2016) - Johnston, Shawn; Candelier, Alexis; Powers-Green, Dana; Johnston, Gabriel
ABSTRACT: Court-ordered psychological evaluations of criminal defendants generally include two types: mental status (competence or sanity) versus risk assessment. When defendants are deceptive in mental status evaluations, lies of commission, in which symptoms of psychopathology are feigned (malingering), are most likely. When defendants are deceptive in risk assessments, lies of omission, in which antisocial impulses are concealed or denied, are most likely. Four research conditions, consisting of the true and false statements of two men accused of sex offenses and two men claiming an insanity defense, were rated by participants on a test of truthfulness containing eight items derived from Criterion-Based Content Analysis and Reality Monitoring. All items, as well as the collective test score, significantly differentiated between true and false statements. Further, the lie of commission was rated as significantly more false than the lie of omission, and a confession was rated as more truthful than a true statement involving only exculpatory information, which is in accordance with the theory of cognitive load. Factor analyses provided support for the construct validity of the test of truthfulness and two subscales. Further, the data suggests that statements judged true are characterized by the presence of attributes of truthfulness, while statements judged false are characterized by the absence of attributes of truthfulness along with the presence of attributes of untruthfulness.